Natural triterpenoids from licorice potently inhibit SARS-CoV-2 infection - Yang Yi; Li, Junhua; Xinyuan Lai; Meng Zhang; Yi Kuang; Yang-Oujie Bao; Rong Yu; Wei Hong; Elishiba Muturi; Heng Xue; Hongping Wei; Li, Tong; et al. (J Adv Res ., 2021)
Introduction: The COVID-19 global epidemic caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2) is a great public health emergency. Discovering antiviral drug candidates is urgent for the prevention and treatment of COVID-19. Objectives: This work aims to discover natural SARS-CoV-2 inhibitors from the traditional Chinese herbal medicine licorice. Methods: We screened 125 small molecules from Glycyrrhiza uralensis Fisch. (licorice, Gan-Cao) by virtual ligand screening targeting the receptor-binding domain (RBD) of SARS-CoV-2 spike protein. Potential hit compounds were further evaluated by ELISA, SPR, luciferase assay, antiviral assay and pharmacokinetic study. Results: The triterpenoids licorice-saponin A3 (A3) and glycyrrhetinic acid (GA) could potently inhibit SARS-CoV-2 infection, with EC50 of 75 nM and 3.17 µM, respectively. Moreover, we reveal that A3 mainly targets the nsp7 protein, and GA binds to the spike protein RBD of SARS-CoV-2. Conclusion: In this work, we found GA and A3 from licorice potently inhibit SARS-CoV-2 infection by affecting entry and replication of the virus. Our findings indicate that these triterpenoids may contribute to the clinical efficacy of licorice for COVID-19 and could be promising candidates for antiviral drug development. Keywords: COVID-19; Glycyrrhetinic acid; Licorice; Licorice-saponin A3; SARS-CoV-2.